Estructural components of teachers' attitudes towards integration Digital Interactive Table (DIT) in the classroom - Ana Belén SÁNCHEZ GARCÍA (Ediciones Universidad de Salamanca, 2015)
The aim of this paper is to assess attitudes toward the integration of the Digital Interactive Table (DIT) in the classroom. We wonder if there is a positive predisposition towards such integration, and if it is linked to attitudes in their cognitive, affective-emotional and behavioral aspects. To this end, we propose a multicasual study based on the collection of qualitative data obtained through recordings on two semi-structured interviews with teachers to initiate and complete their training in the use of the Digital Interactive Table. The results point toward the existence positive attitudes.